1994
DOI: 10.1042/bj3020827
|View full text |Cite
|
Sign up to set email alerts
|

Structure, expression and gene sequence of a juvenile hormone esterase-related protein from metamorphosing larvae of Trichoplusia ni

Abstract: A carboxylesterase with an encoded molecular size of 61 kDa and a high sequence similarity to juvenile hormone esterase (JHE) has been cloned from cDNA prepared from final instar larvae of Trichoplusia ni. The absence of a recognizable encoded signal peptide suggests that the enzyme, JHER (for JHE-related) may not be secreted, in contrast to JHE. When the amino acid sequence of JHE, JHER and other esterases were mapped onto the secondary and tertiary structure determined crystallographically for acetylcholines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 61 publications
1
9
0
1
Order By: Relevance
“…In this respect the expression of JHER appears similar to that reported for certain other genes that are highly expressed before, but not after, metamorphic commitment, such as the arylphorin gene that is controlled by ecdysteroids (Jones et al, 1994). It is suggested that, TniJHE and TniJHER are physically juxtaposed in T. ni (Jones et al, 1994).…”
Section: Plasmids and Virus Constructssupporting
confidence: 57%
See 3 more Smart Citations
“…In this respect the expression of JHER appears similar to that reported for certain other genes that are highly expressed before, but not after, metamorphic commitment, such as the arylphorin gene that is controlled by ecdysteroids (Jones et al, 1994). It is suggested that, TniJHE and TniJHER are physically juxtaposed in T. ni (Jones et al, 1994).…”
Section: Plasmids and Virus Constructssupporting
confidence: 57%
“…Moreover, if cells were treated with tunicamycin (a strong inhibitor of N-linked glycosylation), the apparent size of the immunopositive bands decreased to 60 kDa. As is the case for all JHE and JHER proteins studied so far (Jones et al, 1994), SnJHER also contains glycosylation sites [NX(S/T)] in its predicted protein sequence (Kontogiannatos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The similarities are particularly extensive in the N-terminal halves of the enzymes, and computer analysis also showed that JHE contains a serine active site, common to hydrolases. This information indicates an evolutionary relationship between JHE and other esterases (Hanzlik et al, 1989;Jones et al, 1994), and suggests that carboxylesterases may have evolved by gene amplification and divergence. A better understanding of the phylogenetic relationships of the different esterases will be possible once more information on the primary sequences of JHEs and other esterases becomes available.…”
Section: Jh Specific Esterasesmentioning
confidence: 96%